Desarda Versus Lichtenstein Repair for Primary Inguinal Hernia in Men: Results of A Randomized Control Trial (Faridpur Medical College Journal, 2020)
Inguinal hernia is a very common surgical problem for which mesh based technique particularly Lichtenstein repair is considered as standard. However, it is not free from some major and bothersome complications. Desarda technique of non-mesh hernia repair invented by the Indian surgeon is claimed as low cost tension free procedure with promising results. The objective of the study is to evaluate the feasibility of Desarda procedure in country like Bangladesh as a treatment of primary inguinal hernia in men by comparing with Lichtenstein repair in terms of various parameters. One hundred and sixty male patients between ages of 18-70 years with uncomplicated primary inguinal hernia were initially randomized to perform the one of the two procedures in every alternate patient. Outcome were measured and analyzed. A total of 100 patients were finally studied with a follow up of 2 years. Operative time and immediate postoperative pain were significantly less in Desarda arm. Cost and foreign body sensation were also in favour of Desarda group. There was no recurrence in either group. Desarda repair is easy to perform and takes less time. It is cost effective with a comparable clinical outcome to standard Lichtenstein repair at least in short term.Faridpur Med. Coll. J. Jan 2019;14(1): 20-26